Studi Karakteristik Sereal Breakfast Flakes Dari Variasi Konsentrasi Tepung Beras Merah Dan Tepung Edamame Dengan Perbedaan Perlakuan Pengukusan - Umiyati, Rini; Finda Evita Marviana; Rizky Muliani Dwi Ujianti; Fafa Nurdyansyah (Jurnal Sains Boga, 2025)
Flakes are a food innovation that can be made from tubers, seeds, nuts and other horticultural plants which people like because they are easy to consume and practical in serving. The aim of this research is to determine the optimal formulation in making brown rice flour breakfeast cereal flakes products with edamame flour substitution and determine the effect of steaming and non-steaming treatments on the physicochemical and organoleptic characteristics of brown rice flour breakfast flakes cereals with edamame flour substitution. The experimental design used in this research was a completely randomized design with 3 replications. The experimental design consists of 2 factors, namely the ratio of brown rice flour and edamame flour which consists of 3 formulations, namely Formulation 1 (50g:50g), Formulation 2 (60g:40g), Formulation 3 (70g:30g) and the difference in processing before baking, namely by steamed and oven and directly oven. The analysis in this research is chemical analysis such as water content analysis, ash content analysis, fat content analysis, protein analysis, crude fiber analysis. Physical analysis such as analysis of texture, water absorption, durability in milk and organoleptic analysis includes descriptive and hedonic analysis with the attributes of color, aroma, taste and texture. The results showed that the addition of high levels of edamame flour and brown rice flour and the steaming process were significantly different in water content, ash, protein fat, crude fiber, calorific value, carbohydrates, water absorption capacity, texture, durability in milk.